ANALISA PROSES PRODUKSI, KOMPOSISI KARYAWAN TERHADAP PRODUKTIVITAS PADA PT. ANGELS PRODUCTS, BOJONAGARA, SERANG, BANTEN - herwinda Astuti; Vira Saskia Putri; Rizky Zahrowi; Ady Eldiwan; Bajongga Apriyanto; Dutiks Dian Utami Dewi; Sarah Kristin Mailini; Jauhari jauhari; Rima Yulianti; Sultia Linika Sari; Tuana Resmin Florentina; Juparna Purba; Salman Yulianto; Bomer Pasaribu; Partogi S. Samosir; Eddy Sanusi Silitonga (SIKAMA : Sinergi Akademisi dan Masyarakat, 2023)
Refined sugar is sugar that comes from refining raw sugar or raw sugar and then recrystallizes it. Refined sugar may only be used for industry based on the Decree of the Minister of Industry and Trade no 527/MPT/KET/9/2004, refined sugar is prohibited from being sold for household consumption because it has to go through further processing. With a production capacity of 5.5 million tons per year, the utility rate is around 60 percent to meet the needs of 3 million tons per year. The government must issue import approvals (PI) for refined sugar raw materials for industrial needs and the continuity of the Company's operations. The purpose of this research is to: Identify external and internal environmental factors that can become opportunities, threats, strengths and weaknesses of the company in competing with similar companies by analysing related production processes and company productivity seen from the results of the refined sugar melting capacity produced by the company.annually . The research method uses study literature and is based on direct observation and question and answer (secondary data) at PT Angels Product having its address at Bojonagara, Tangerang